PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN DANA DESA MELALUI PENGUATAN KELEMBAGAAN - Zulkarnaini, Zulkarnaini; Mashur, Dadang (Jurnal Kebijakan Publik, 2018)
Community Empowerment in the Utilization of Village Funds through InstitutionalStrengthening. Until now there are still many problems in rural development in Indonesia that needto find a solution. One of the government's efforts to accelerate village development is by rolling outthe Village Fund Allocation Program (ADD) to realize the administration and implementation ofaspirative and participatory village development. In Siak District, the ADD program has been heldsince 2007, but until now its implementation has not been optimal yet. This study aims to determinehow the empowerment of community in the utilization of ADD through institutional strengtheningDistrict Apit Sungai Siak District and what factors affect the effort of empowerment. This researchis a descriptive qualitative research with sampling technique used is snowball sampling. The researchinformants were the officials involved in the ADD program and the community leaders who knewthe program. Data collection was done by interview and observation technique, after the datacollected and then analyzed by using qualitative descriptive analysis. The results show thatcommunity empowerment through ADD Program in Sungai Apit Subdistrict of Siak Regency hasnot been running well. Many of these programs are diverted to village infrastructure developmentprograms rather than community empowerment activities. The dominant factor influencing themismatch of community empowerment is the fear of failure resulting from the inability of thecommunity to join the ADD program that provides business capital assistance for the needy.